Kepemimpinan Kepala Sekolah Dalam Mendukung Program Edukasi Kesehatan Lingkungan Di SDN Tambaklekok 1 - Lina Mamlu’atul C; Thohir, Muhammad; Mardiyah (Yayasan Cendekia Gagayunan Indonesia, 2024)
This research aims to analyze how the leadership of the school principal at SDN Tambak Lekok 1 supports the implementation of environmental health education programs. The approach used in this research is a qualitative-descriptive approach. Researchers conduct an in-depth study of various phenomena in the field and describe them in the form of words and sentences. The methods used by researchers in collecting data are direct observation, in-depth interviews, and documentation analysis. The research results show that school principals have a significant role in supporting environmental health education programs. The visionary and participative leadership of the school principal plays an important role in planning, implementing and evaluating the program. The school principal is also active in facilitating the formation of environmentally friendly school policies, providing cleaning facilities, as well as collaborating with related agencies and the local community. Effective school principal leadership is key to the success of environmental health education programs. This research suggests that school principals continue to improve their leadership capacity, especially in terms of managing environmental programs, as well as involving more stakeholders, such as parents and the surrounding community. Environmental health education in elementary schools is an important aspect in forming environmental awareness and behavior from an early age. The leadership of the school principal plays a role in the successful implementation of this educational program.